A Gambaran Osteitis Fibrosa Pada Seorang Penderita Dengan Gangguan Mineral Tulang Pada Penyakit Ginjal Kronik (Chronic Kidney Disease – Mineral Bone Disorder) : CKD MBD : Bagaimana mendeteksi, mencegah dan pengobatannya - Ifan Distyajaya Anak Agung (Jurnal Medika Hutama, 2023)
Chronic Kidney Disease–Mineral and Bone Disorder (CKD-MBD) is a common complication that occurs in CKD in the early stages of the disease. This condition can persist and progress as the CKD stage increases. Bone biopsy is still considered as the gold standard tool in determining the mechanism of turnover, mineralization and bone volume defects in CKD patients. Currently, CKD-MBD and its complication management have been focusing on correcting biochemical and hormonal abnormalities to limit their potential effects This case is a picture where the diagnosis can be established clearly and gave the proper management. We report a case with CKD-MBD and received comprehensive treatment of internal medicine and orthopaedic surgery so that the patient was able to improve on laboratory and physical activity. Seeing the importance of the relationship between CKD and its progression towards CKD-MBD, it is necessary to make an accurate and effective diagnosis early to determine the right therapy so as not to fall into side effects or fatal complications. The proper diagnosis and treatment of CKD is very important because it is often associated with morbidity or mortality.